Plastic waste impact and biotechnology: Exploring polymer degradation, microbial role, and sustainable development implications - Isra E. Gilani (17019066) (2023)
The significant impact of plastic waste on ecosystems has raised concerns regarding its detrimental effects. This review examines the various types of synthetic and degradable plastics and explores the physiochemical properties of polymers during degradation. It delves into the management of plastic waste, considering both abiotic and biotic degradation mechanisms. Biotic degradation, including aerobic and anaerobic pathways, is also examined, with a specific focus on the role of microorganisms and their enzymes in facilitating biodegradation. The review further explores the biotechnological implications of plastic waste management, including gene manipulation, genetic modification, and the potential of anaerobic biotechnology. It emphasizes the importance of transitioning toward a circular economy and highlights the alignment of these efforts with sustainable development goals (SDGs). Overall, this review provides insights into the impact of plastic waste on the environment, explores degradation mechanisms, and discusses biotechnological approaches and sustainable practices aimed at addressing the challenges posed by plastic waste. Other Information Published in: Bioresource Technology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biteb.2023.101606